2023
DOI: 10.1111/jir.13012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the fundamental movement skill proficiency of children with intellectual disabilities and typically developing children: a systematic review and meta‐analysis

Abstract: BackgroundChildren around the world, particularly those with intellectual disabilities (ID), are exhibiting poor motor skill proficiency. Compared with typically developing children (TDC), children with intellectual disabilities (CwID) are 65% more likely to exhibit low levels of motor competence. The purpose of this meta‐analysis was to compare the motor skill proficiency levels, in terms of fundamental movement skills (FMS) of CwID to TDC. FMS are the building blocks required for lifelong participation in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 85 publications
1
8
2
Order By: Relevance
“…Additionally, Bolger et al (2018) recommended the introduction of annual formal assessments of FMS for children in primary schools to monitor motor competence over time, as seen in many countries across Europe. This idea could potentially be implemented by trained coaches in community sports clubs with support from volunteers or parents, particularly for children with intellectual disabilities who have exceptionally low motor competence (Kavanagh et al, 2023). These assessments would provide encouragement to sports coaches to develop and improve the motor competence of children with intellectual disabilities, enable coaches to track the progress of each child in their session, as well as highlight to parents' particular skills which require continued work and development (Bolger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Bolger et al (2018) recommended the introduction of annual formal assessments of FMS for children in primary schools to monitor motor competence over time, as seen in many countries across Europe. This idea could potentially be implemented by trained coaches in community sports clubs with support from volunteers or parents, particularly for children with intellectual disabilities who have exceptionally low motor competence (Kavanagh et al, 2023). These assessments would provide encouragement to sports coaches to develop and improve the motor competence of children with intellectual disabilities, enable coaches to track the progress of each child in their session, as well as highlight to parents' particular skills which require continued work and development (Bolger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying movement deficiencies and implementing interventions to target these weaknesses during the childhood years is invaluable to helping establish lifelong engagement in sport and physical activity (Ward et al, 2020), particularly for children with intellectual disabilities who exhibit low levels of FMS performance which can impact quality of life (Kavanagh et al, 2023). FMS assessment therefore plays an important role in helping practitioners and researchers to understand movement skill proficiency as well as informing interventions (Barnett et al, 2009; Logan et al, 2015; Ward et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have functional di culties during walking and other locomotor movement forms (e.g., single-leg jump, sliding). A recent systematic review and meta-analysis by Kavanagh et al (2023) [15] showed that the standardized mean difference in FMS between typically developing children and children with ID is large, especially for the total locomotor score, object control score, balance, and running and throwing skills. They also exhibit lower manual dexterity related to motor control of the hand, including brushing their teeth and tying their shoe laces [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that developmental disabilities such as ID, ASD, and ADHD often co-occur ( 7 ). Recent studies show that children with developmental disabilities have below-average fine motor skills compared to their age group ( 4 , 5 ). Children with developmental disabilities also tend to have more motor impairments than typically developing (TD) children ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%